PARENTING PATTERNS AND NUTRITIONAL STATUS OF TODDLERS BASED ON TB/U INDICATORS - Saleh, Asmulyati S; Niron, Maria F.Vinsensia D.P Kewa (Kupang Journal of Food and Nutrition Research, 2024)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time. The problem of stunting nutrition is caused by the mother's lack of nutritional knowledge and improper parenting. Based on data from the health center in February 2023 in Oenesu Village, the nutritional status based on the TB / U indicator of toddlers has a short nutritional status of 15 people (18.9%) and a very short nutritional status of 3 people (3.7%). The purpose of the study was to determine the relationship between parenting patterns and nutritional status based on TB / U indicators in toddlers aged 24 - 59 months in Oenesu Village, West Kupang District, Kupang Regency. This study used quantitative methods with a cross sectional design. The research was conducted in January - February 2023 in Oenesu Village. The sample in this study were mothers and toddlers aged 24 - 59 months as many as 53 people with total sampling technique. The research instrument used was a parenting questionnaire. The variables in this study were the nutritional status of TB/U indicators and parenting patterns. Data analysis using univariate analysis and bivariate analysis conducted with Ficher's exact test. The results showed that parenting patterns of feeding were lacking 1 person (1.9%) and parenting patterns of health service utilization were lacking as many as 14 people (26.4%). Conclusion: There is no significant relationship between feeding parenting and health service utilization parenting with nutritional status.